2016
DOI: 10.1111/cobi.12738
|View full text |Cite
|
Sign up to set email alerts
|

Plant blindness and the implications for plant conservation

Abstract: Plant conservation initiatives lag behind and receive considerably less funding than animal conservation projects. We explored a potential reason for this bias: a tendency among humans to neither notice nor value plants in the environment. Experimental research and surveys have demonstrated higher preference for, superior recall of, and better visual detection of animals compared with plants. This bias has been attributed to perceptual factors such as lack of motion by plants and the tendency of plants to visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
188
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(207 citation statements)
references
References 66 publications
(111 reference statements)
7
188
0
12
Order By: Relevance
“…The categorization of mentions into the three main categories was considered to be unproblematic as they are distinctly different. However, the coding of mentions into the subcategories was subjected to repeated readings of the answers given and negotiated between the coders and the theoretically grounded aspects of mentions relating to plants and animals (e.g., Knight, ; Balding & Williams, ) and from studies regarding humans and plants (e.g., Sanders, ; Balding & Williams, ). This process is similar to the one presented in Andersson and Wallin (); “[the] categories emerge by a process of hypothesizing them and checking them against actual answers”.…”
Section: Analysesmentioning
confidence: 99%
“…The categorization of mentions into the three main categories was considered to be unproblematic as they are distinctly different. However, the coding of mentions into the subcategories was subjected to repeated readings of the answers given and negotiated between the coders and the theoretically grounded aspects of mentions relating to plants and animals (e.g., Knight, ; Balding & Williams, ) and from studies regarding humans and plants (e.g., Sanders, ; Balding & Williams, ). This process is similar to the one presented in Andersson and Wallin (); “[the] categories emerge by a process of hypothesizing them and checking them against actual answers”.…”
Section: Analysesmentioning
confidence: 99%
“…Schwarz et al () found that when analyzing seven major cities, the authors found a strong relationship between urban tree cover and income: the lower the income, the fewer the trees. Decision‐makers may underestimate the importance of trees and plants in humanitarian work due to bias of plant blindness (Balding & Williams, ), but this paper illustrates the benefits.…”
Section: Important Considerationsmentioning
confidence: 79%
“…In other words, students represented grass as either a “stem,” indicated as a single drawn line or series of lines; or a leaf, indicated by a triangular shape or series of triangular shapes. These common mental models found within the children's drawings for plant, tree, flower, and grass represent what are likely cultural and location influenced archetypes to create a mental model based on what is available and emotionally relevant to the student (Balding and Williams, 2016; Bartoszeck et al, 2015; Tunnicliffe and Reiss, 2000).…”
Section: Resultsmentioning
confidence: 99%